Self-preserving behavior in the student environment as a way to cope with bad habits - Svetlana A. Tyaglova; Anton A. Ryabykh (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper examines the genesis and causes of bad habits spread among students (external and internal), provides a review of the scientific literature on the research topic. Medicine has proved that bad habits as a risk factor for various infectious diseases and deterioration of all body systems functionality result in reducing the quality and duration of human life. Scientists agree that in order to solve the problem of adopting bad habits by young people there should be an integrated approach combining the regularity of preventive measures and the united intention of all participants in the educational process. The aim of the study is to develop a prevention model based on the study of the structure and genesis of bad habits in the student environment. To determine the state of the problem, the authors conducted a study among 3 and 4-year students of the technical university (55 people aged 18-25 years), identifying the most common harmful addictions during training and their prerequisites according to the students opinion. The most common habit is smoking, followed by poor nutrition, lack of sleep and alcohol. Moreover, many habits were acquired in adolescence and college period. Most students are neutral about other peoples having such habits. Based on the results obtained, possible solutions of the problem are presented in the context of self-preserving behavior of students, actualizing the possible potential ofa positive influence of the university environment on increasing personal awareness through the education of its qualities and a positive example of the environment.